Understanding the Ni Migration in Solid Oxide Cell: A Coupled Experimental and Modeling Approach. Issue 3 (17th March 2023) - Rorato, Léa; Shang, Yijing; Yang, Shenglan; Hubert, Maxime; Couturier, Karine; Zhang, Lijun; Vulliet, Julien; Chen, Ming; Laurencin, Jérôme
Abstract : A long-term test of 2000 h has been carried out on a typical solid oxide cell in electrolysis mode at −1 A.cm −2 and 750 °C. The 3D reconstructions of the pristine and aged cermet have revealed a strong Ni depletion at the electrolyte interface. To explain this result, an electrochemical and phase-field model has been developed to simulate the Ni migration in Ni/YSZ electrode. For this purpose, a mechanism has been proposed that takes into account the impact of polarization on the Ni/YSZ wettability. In this approach, it assumes that the Ni/YSZ interfacial energy is changed by the concentration of oxygen vacancies in the electrochemical double layer. Thanks to the model, the Ni migration has been computed in the same condition than the experiment and complemented by a simulation in reverse condition in SOFC mode. In good agreement with the experiment, the simulations have revealed a strong Ni depletion at the electrolyte interface after operation under electrolysis current. On the contrary, a negligible Ni redistribution with a very slight Ni enrichment has been predicted at the electrolyte interface after SOFC operation. These results tend to prove the relevance of the mechanism.